Performance of gladiolus cultivars under sub-humid southern plains of Rajasthan - T.C. Mahawer (Journal of Horticultural Sciences, 2013)
An investigation was carried out during October 2011 - May 2012 to evaluate performance of 15 cultivars of gladiolus for cut-flower, corm and cormel production. Cultivar ‘IIHR-G-12’ gave maximum plant height (108.32cm), spike length (76.43cm), rachis length (58.27cm), number of florets per spike (14.90), number of florets open at a time (3.63), longevity of florets (3.39 days), vase life of spike (14.20 days), number of spikes per plant (2.50), field durability of spike (16.20 days), flowering duration (38.20 days), number of corms per plant (2.55), corm diameter (6.13cm) and fresh weight of cormels per plant (29.42g); while, cv. ‘Gunjan’ gave largest floret diameter (10.39cm) and cormels per plants (60.76). Earliness in heading (65.87 days), spike emergence (70.43 days), first floret showing colour (82.93 days) and basal floret opening (85.60 days) were observed in cv. ‘IIHR-G-12’. Significantly high corm fresh weight (70.24g) and leaf width (3.28cm) were noticed in cv. ‘Pusa Kiran’. However, largest cormel diameter (1.91cm) was seen in cv. ‘Delhi Pink’, maximum number of tillers per plant in cv. ‘Punjab Dawn’, whereas, number of leaves plant-1 (9.60) and leaf length (40.41cm) were recorded in cv. ‘Dhanvantari’. Among the cultivars tested, cv. IIHR-G-12 was found to be the best for significantly high spike yield (4.17 lakh), corm yield (4.25 lakh) and cormel yield (49.03q) ha.